Analysis of Business Development Strategies as an Effort to Increase the Selling Value of Souvenirs Typical of Tanjung Bira Beach Bulukumba District - Ilham Abu; Ridwan Ridwan; Nur Halim (Indonesian Journal of Business and Entrepreneurship Research, 2023)
This study aims to determine and analyze the souvenir business development strategy, especially in the souvenir carving business typical of Tanjung Bira Beach which is appropriate so as to increase the selling value. This research is categorized as qualitative descriptive research using SWOT analysis, namely the IFAS and EFAS matrix which are identified as important factors from both the internal environment and the external environment in the form of strengths, weaknesses, opportunities, and threats from the typical souvenir business of Tanjung Bira Beach. Based on the results of the analysis, the strategy generated in this study is in quadrant 1 (one), namely the aggressive or growth strategy quadrant (growth-oriented strategy), where the total score of strengths and weaknesses is 2.95 while the total score of opportunities is 2.94. The position of this quadrant is very favorable because it can be maximally marketed by implementing marketing mix policies such as improving product quality, expanding promotions, maintenance, and improving service quality that support the aggressive growth of business products typical of Tanjung Bira Beach.